PELAKSANAAN KATEKESE SEKOLAH MINGGU DALAM MENGEMBANGKAN IMAN ANAK DI PAROKI SANTU JOSEF ONEKORE KECAMATAN ENDE TENGAH KABUPATEN ENDE - Boleng, Benedikta (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to analyze the implementation of Sunday school catechesis and the development of children's faith in the Santu Josef Onekore Ende Parish. The approach used in this study is a qualitative approach. The methods used in this research are interviews, observation and documentation. The results of the research show that the implementation of Sunday school catechesis is an alternative that really helps the development of children's faith. On this auspicious occasion Christian values began to be instilled in children at an early age so that they were developed and lived out in life, both individually and collectively in society. Sunday school catechesis can lead children to meet their friend Jesus and to meet others every Sunday. Based on the results of this research, it can be concluded that the implementation of Sunday school catechesis is an alternative that really helps the development of children's faith. On this auspicious occasion Christian values began to be instilled in children at an early age so that they were then developed and lived out in life both individually and collectively in society.